Development and Implementation of Web Based Fault Monitoring System, case study: PT. PLN (Persero) Tondano Customer Service Unit - Quido Conferti Kainde (International Journal of Information Technology and Education, 2022)
PLN ULP Tondano has several divisions in which there is the Engineering Division or Distribution Section. Within this division, there are several jobs that are carried out on a daily basis, one of which is monitoring and managing current disturbances that occur around the dependent area. However, technical monitoring even to collect data in order to view daily data is very difficult because office employees have to input what has been reported by field workers, and then the data will be returned again for execution. This is what really slows down the performance because the techniques used are still manual and old. Due to this, the monitoring and archiving process takes a very long time. This also results in the possibility of existing data being lost because the data is still inputted manually and there is no backup file that can be used if the data disappears at any time. In addition, field officers are also overwhelmed to find out data that is only input manually and firstly which could hamper existing performance.